Research progress on the impact of mineral surface roughness on particle-bubble interaction - Xiangning BU; Zheng TONG; Yujin SUN; Guangyuan XIE; Xianshu DONG (Meitan xuebao, 2023)
Mineral surface roughness is an important factor affecting flotation efficiency. Surface roughness can affect the hydrophobicity of minerals, the adsorption of reagents, and the rupture of liquid films between particles and bubbles, resulting in a significant impact on the interaction process between particles and bubbles. However, there is currently a lack of systematic review work on the influence of roughness on particle-bubble interaction process. Therefore, the authors firstly reviewed the surface roughening modification techniques and roughness testing methods. Secondly, the influence of roughness on the particle-bubble interaction process was systematically discussed from four aspects: flotation kinetics, contact angle, formation time of triple-phase contact line, and interaction force between particles and bubbles. The concept of roughness scale was proposed for its importance in the research of particle-bubble interactions. Thirdly, based on the coupling mechanism between roughness scale and mineral surface hydrophobicity in the particle-bubble interaction process, the importance of mineral surface wetting state in the interaction process between rough surfaces and bubbles was emphasized. The reasons for the inconsistent research conclusions on the impact of roughness on contact angle and flotation performance were also analyzed and discussed. Finally, the conclusions were drawn through critical analysis and literature review, and the prospects for future research directions were outlined. This paper contributes to a better understanding of the influence of mineral surface roughness on the flotation process, and can provide a theoretical support for regulating mineral surface roughness to create favorable flotation conditions and improve the flotation efficiency and selectivity.